ANALYSIS OF BRAZILIAN LEGISLATION CRITERIA ON THE GUARANTEE OF ACCESS TO EDUCATION - MENDES, ROSELAINE GUSSON (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
The focus of this bibliographical analysis dazzles the evolution and inconsistency of legal norms on the mandatory education system for childhood in Brazil. Considering the concerns of access, permanence and quality of the services provided, perceiving a constant, progressive development of access to this right, even though there are still challenges for its universalization. Bad working conditions, lack of government policies, uncertainty in the preparation and effectiveness of teachers are identified as structuring challenges for education in Brazil. In this way, we understand that it is still necessary to reflect and create strategies for implementing public policies, to guarantee conditions of permanence and qualified learning for all children and adolescents.